An Equilibrium Model of Asset Pricing and Moral Hazard - Ou-Yang, Hui (Review of Financial Studies, 2005)
This article develops an integrated model of asset pricing and moral hazard. It is demonstrated that the expected dollar return of a stock is independent of managerial incentives and idiosyncratic risk, but the equilibrium price of the stock depends on them. Thus, the expected rate of return is affected by managerial incentives and idiosyncratic risk. It is shown, however, that managerial incentives and idiosyncratic risk affect the expected rate of return through their influence on systematic risk rather than serve as independent risk factors. It is also shown that the risk aversion of the principal in the model leads to less emphasis on relative performance evaluation than in a model with a risk-neutral principal. Copyright 2005, Oxford University Press.